2021
DOI: 10.1177/19322968211034533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Digital-Tool-Supported Basal Insulin Titration Algorithm in Reaching Glycemic Control in Patients with Type 2 Diabetes in Mexico

Abstract: Background: My Dose Coach (MDC) is a mobile application combined with a web portal that can suggest optimized basal insulin (BI) injection doses using Self-Measured Plasma Glucose (SMPG) and hypoglycemia data. This study aimed to evaluate its efficacy on patients reaching SMPG and Fasting blood glucose (FBG) target range 90-130 mg/dl (5-7.2 mmol/L) goals without severe hypoglycemic episodes. We also addressed the mean reduction in glycated hemoglobin (A1C), FBG, and SMPG and the improvement in the WHO’s Five W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…As recommended by the World Health Organization, 32 there is a need to strengthen the use of digital technology and other resources for improving the clinical management of diabetes, such as My Dose Coach, a digital app that supports people with T2D during basal insulin titration. 33 Importantly, the results from ATOS LATAM should be interpreted with caution because of several limitations, consisting of the small sample size, a lack of randomization and the lack of a comparator arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As recommended by the World Health Organization, 32 there is a need to strengthen the use of digital technology and other resources for improving the clinical management of diabetes, such as My Dose Coach, a digital app that supports people with T2D during basal insulin titration. 33 Importantly, the results from ATOS LATAM should be interpreted with caution because of several limitations, consisting of the small sample size, a lack of randomization and the lack of a comparator arm.…”
Section: Discussionmentioning
confidence: 99%
“…As recommended by the World Health Organization, 32 there is a need to strengthen the use of digital technology and other resources for improving the clinical management of diabetes, such as My Dose Coach, a digital app that supports people with T2D during basal insulin titration. 33 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 In a pilot study of 158 patients with T2DM using the digital health tool in Mexico, 58.9% of participants reached their target self-measured plasma glucose level with a mean reduction of 30.9 mg/dL. 20 Target fasting blood glucose level was reached in 55.7% of participants with a mean reduction of 63.4 mg/dL and no severe hypoglycemic events. HbA1c was reduced by 1.78% on average with the last observation carried forward.…”
Section: Self-efficacymentioning
confidence: 99%
“…This health tool has already been implemented in India and Mexico and evaluated in independent pilot studies. [20][21][22] The results from these studies demonstrated that the use of this digital health tool successfully decreased HbA1c levels, achieved easier target fasting blood glucose levels, and improved overall well-being without any severe hypoglycemic events. [20][21][22] The aim of this multicenter randomized controlled study is to investigate the effectiveness of using this digital health tool in improving glycemic control as a medical benefit and patient-relevant structural and procedural improvements, as assessed by patient-reported outcomes via the implementation of the physician-determined titration algorithm in patients' daily lives within the German healthcare system.…”
Section: Introductionmentioning
confidence: 99%